PEMBANGUNAN YANG KAPITALISTIK, DAMPAK TERHADAP EKOLOGI DAN KEHIDUPAN MANUSIA - Jayanti, I Gusti Ngurah (PIRAMIDA, 2012)
Development, principally, relieves human from pressure and exploitation. Practically in the social structure, it is variably translated, and consequently the term development seems to be ambivalence which is strongly based on various interests in the society. In reality, development can not be separated from links of authority and interests that construct it in 1habitués and cultural histories, so the development emerges in different forms. In the third world, it is clear that development issue undergoes pressure from dominantly ideological construction that emerges from the domain and social condition of western countries. The expansion of western ideology through colonial imperialism left over some sedimentation which strongly influences the way of thinking of the people in the third world. The influence can be seen from economic policy system in some part of developing countries, which adopt the western country’s economic system. Capitalism system is a form of which has been absorbed in the regulation of economic development sector. It is showed out that the implementation of capitalism system causes some excess in many sectors not only in economic, but becomes wider in the social cultural in the internal third world countries and it does as well in Indonesia. Development pattern that focuses only on one sector or capitalist economic determinism brings about some excess in many other sectors. The structure is not in line with the spirit and character of multicultural nation. Consequently, defining on the structure of development and criticizing the structures policy of developed industrial nations, toward development especially in Indonesia is urgently required.
Keywords: development, capitalism, and ecology 1